Osteoporosis and bone metabolism in cirrhotic patients - Enver GÜREL,; Mahmut ÖZTÜRK,; Macit GÜLTEN,; Selim Giray NAK,; Enver DOLAR,; Yusuf KARAARSLAN,; Faruk MEMİK, (Turkish Journal of Gastroenterology, 2019)
-